High density tungsten gadolinium borate glasses doped with Eu3+ ion for photonic and scintillator applications. (July 2020) - Wantana, N.; Kaewnuam, E.; Ruangtaweep, Y.; Kidkhunthod, P.; Kim, H.J.; Kothan, S.; Kaewkhao, J.
Abstract: The melt quenching technique used to prepare tungsten gadolinium borate (Eu: WGdB) glasses doped with different concentrations of Eu 3+ ions. The structural and spectroscopic analysis have been carried out by density, molar volume, X-ray absorption spectroscopy (XAS), UV-VIS-NIR absorption, excitation, emission spectra and decay time measurements. The glasses containing WO3 exhibit a high density of more than 6.00 g/cm 3 and performs the enhanced compaction with increment of Eu2 O3 content. The average coordination number of oxygen surrounding Eu 3+ is 6.000 and the average bond length between Eu 3+ and oxygen is 2.3740 Å. Eu 3+ in glass absorb photons in visible light and near infrared region. The strong reddish orange emission around 613 nm via 5 D0 → 7 F2 radiation transition of Eu 3+ was generated under different types of excitation such as ultraviolet, visible light and X-ray. The Gd 3+ - Eu 3+ energy transfer has an important role for strong reddish orange emission under 275 nm excitation. The Judd-Ofelt (J-O) theory was used to predict the radiative properties for the Eu 3+ ion emission levels. The decay curves of the 5 D0 levels exhibit single exponential nature with a lifetime of millisecond order. The high stimulated emission cross-section and intense emission with 613 nm wavelength suggests that the present Eu-WGdB glasses could be useful for the solid-state laser, display devices and radiation detecting material applications. Highlights: New high-density WO3 -Gd2 O3 –B2 O3 :Eu 3+ glasses were prepared. Eu 3+ in glass is surrounded by the first shell of six oxygen neighbors and the average Eu–O bond length is 2.372 Å. The high stimulated emission cross-section of glass performs the promising candidate for laser medium applications. The energy transfer of Gd 3+ → Eu 3+ and [WO6 ] 6- → Eu 3+ plays the important role for using glass as radiation detecting material.